Photodiode and photocapacitor properties of Au/CdTe/p-Si/Al device - Dahlan, Ammar Sadik; Tataroglu, A.; Al-Ghamdi, Ahmed A.; Al-Ghamdi, Attieh A.; Bin-Omran, S.; Al-Turki, Yusuf; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2015)
The electrical and photoconductivity properties of CdTe on p-type silicon photodiode were investigated by current-voltage (I-V) and capacitance time (C-t) measurements. The current-voltage (I-V) and capacitance-time(C-t) characteristics of the fabricated photodiode were recorded at various illumination intensities in the range of 10-100 mW/cm(2). It is observed that the reverse current of the photodiode increases with increase in illumination intensity. The value of transient photocurrent, photocapacitance and photoconductance increases after illuminating and returns to original value after turning off the illumination. The frequency dependence of the C and G indicates the existence of interface states at metal-semiconductor interface. The obtained results suggest that the fabricated photodiode can be used for photovoltaic and optoelectronic applications. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Photodiode; Cadmium telluride (CdTe); Transient photocurrent